Stakeholders, Bargaining and Strikes - Michael A. Shields; Stephen Wheatley Price (Institute for the Study of Labor (IZA), 2001)
We study bilateral bargaining problems with interested third parties, the stakeholders that enjoy benefits upon a bilateral agreement. We explore the strategic implications of this third party involvement. Our main finding is that the potential willingness of the stakeholder to make contributions to promote agreement may be the source of severe inefficiency. However, and more surprisingly, for a wide range of parameter values this outcome is better for the stakeholder than if he enters bargaining directly. Our results lend support to the tendency towards decentralisation of pay bargaining in the public sector in Europe.
Keywords: C78; 330; Bargaining; public sector; stakeholders; strikes; labour relations; Verhandlungstheorie; Öffentlicher Dienst; Lohnverhandlungstheorie; Streik; Agency Theory; Stakeholder; Firmentarifvertrag; Theorie